Pembangunan Berkelanjutan Ekosistem Dan Pendekatan Nilai Jasa Lingkungan Gili Indah Lombok Utara - Rahman, Fatuh; Johari, Harry Irawan (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
This study purposed knew most important are infrastructure development and the value of services, government policies even often disastrous. When the weakness on the other hand is that it is low or even weak in assessing a product, the function of natural resources is seen as one eye which results in a disaster that must be the work of the government, society, and individuals. Several things trigger disasters to cause damage to works such as road widening, road/bridge construction,. SDA consists of Natural Resources, Biological Resources, Artificial Resources, Humans. In the process of development in developing countries, it prioritizes the use of natural resources for welfare, to increase living standards and welfare through the production process and to reduce environmental pollution. Preservation of environmental functions (planting mangroves) which was carried out a few years ago leaves a story, now it has turned into a settlement or opening a recreation area (Gili Trawangan, Gili Meno, Gili Air), economic activities that do not pay attention to long-term benefits, do not care. Availability of natural resources in the North Lombok area is rampant housing areas, increasingly narrow land, rice fields that were previously planted with rice, conversion of office buildings, houses and trade/shop areas. now changing the function that used to be for catchment areasgovernment policies even often disastrous. When the weakness on the other hand is that it is low or even weak in assessing a product, the function of natural resources is seen as one eye which results in a disaster that must be the work of the government, society, and individuals. Several things trigger disasters to cause damage to works such as road widening, road/bridge construction,. SDA consists of Natural Resources, Biological Resources, Artificial Resources, Humans. In the process of development in developing countries, it prioritizes the use of natural resources for welfare, to increase living standards and welfare through the production process and to reduce environmental pollution. Preservation of environmental functions (planting mangroves) which was carried out a few years ago leaves a story, now it has turned into a settlement or opening a recreation area (Gili Trawangan, Gili Meno, Gili Air), economic activities that do not pay attention to long-term benefits, do not care. Availability of natural resources in the North Lombok area is rampant housing areas, increasingly narrow land, rice fields that were previously planted with rice, conversion of office buildings, houses and trade/shop areas. now changing the function that used to be for catchment areas